App Store Effects on Software Engineering Practices - Al-Subaihin, Afnan A.; Sarro, Federica; Black, Sue; Capra, Licia; Harman, Mark (IEEE transactions on software engineering, 2021)
In this paper, we study the app store as a phenomenon from the developers' perspective to investigate the extent to which app stores affect software engineering tasks. Through developer interviews and questionnaires, we uncover findings that highlight and quantify the effects of three high-level app store themes: bridging the gap between developers and users, increasing market transparency and affecting mobile release management. Our findings have implications for testing, requirements engineering and mining software repositories research fields. These findings can help guide future research in supporting mobile app developers through a deeper understanding of the app store-developer interaction.